Heme: The Lord of the Iron Ring - Vanessa Azevedo Voltarelli; Rodrigo W. Alves de Souza; Kenji Miyauchi; Carl J. Hauser; Leo Edmond Otterbein (MDPI AG, 2023)
Heme is an iron-protoporphyrin complex with an essential physiologic function for all cells, especially for those in which heme is a key prosthetic group of proteins such as hemoglobin, myoglobin, and cytochromes of the mitochondria. However, it is also known that heme can participate in pro-oxidant and pro-inflammatory responses, leading to cytotoxicity in various tissues and organs such as the kidney, brain, heart, liver, and in immune cells. Indeed, heme, released as a result of tissue damage, can stimulate local and remote inflammatory reactions. These can initiate innate immune responses that, if left uncontrolled, can compound primary injuries and promote organ failure. In contrast, a cadre of heme receptors are arrayed on the plasma membrane that is designed either for heme import into the cell, or for the purpose of activating specific signaling pathways. Thus, free heme can serve either as a deleterious molecule, or one that can traffic and initiate highly specific cellular responses that are teleologically important for survival. Herein, we review heme metabolism and signaling pathways, including heme synthesis, degradation, and scavenging. We will focus on trauma and inflammatory diseases, including traumatic brain injury, trauma-related sepsis, cancer, and cardiovascular diseases where current work suggests that heme may be most important.